The Attenuation Ability of Saturated Joints Filled with Granular Materials under High-Amplitude Stress Wave Loading - Sheng Li; Ziming Xiong; Pengxian Fan; Haozhe Xing; Kaidi Xie (Geofluids)
Existing experimental evidence shows that the propagation of explosive waves in the free fields of soils is remarkably affected by the degree of saturation. In the surrounding rocks of underground protective structures, the underground water is normally unavoidable, which is supposed to reduce the isolation efficiency of a passive antiblast barrier. To investigate the effect of water saturation on the stress wave attenuation ability of infilled joints, impact tests were carried out on artificial joints filled with dry and saturated granular materials using a split Hopkinson pressure bar (SHPB). The test results revealed that under the same conditions, the stress and energy transmission coefficients of the waves crossing saturated sand-filled joints were about 3.16–4.13 times and 9.75–11.4 times those of joints filled with dry sand, respectively. The dynamic stress-strain relationship of the filling layer during the impact process and the crushing index of the infill were analyzed. The results showed that the compressibility and the granular crushing index of the dry sand were much greater than that of the saturated sand, and the dynamic stress-strain relationship of the dry sand exhibited three-stage nonlinear characteristics. The experimental results quantitatively uncovered the serious adverse effect of water on the wave absorption properties and markedly diminished the potential of the filled joints as a wave elimination barrier, which should be a matter of great concern in the design of underground protective structures.